Modelling Of Hydrogeological Conditions In Estonian Oil Shale Deposit - The Case Of Dewatering A Surface Mine - H. Lind (Society for Mining, Metallurgy & Exploration, 2006)
The consumption rate of Estonian oil shale increases due to the growing rate of exported oil-shale oil. Estonian oil shale active resources in working mines are predicted until the year of 2025 when the consumption rate stays at the level of 12 tons per year. If the consumption rate stays at that level, new mines should be opened after 20 years, if the rate increases new mines should be opened even earlier. The predicted active resources in Estonian oil shale deposits are calculated for 60 years, based on the parameters of the power station technicoeconomics. As a result, there is a need to open new mines. One of the potential areas for surface mine is the Tammiku-Kose prospect area (Rheinbaun Engineering, 1996).